Media Sosial sebagai Sarana Komunikasi di Era Pandemi Covid-19 di Indonesia - Yonarisman Muhammad Akbar; Dina Fadiyah (Universitas Islam Darul Ulum Lamongan, 2022)
The Covid-19 pandemic, which has caused social and political restrictions on activities, has pushed people to shift their communication virtually. On the other hand, the tendency to interact via social media is increasing. Therefore, this paper discusses more about social media as communication facilities in times of pandemic. Using the Digital Naturals concept and the uses and gratification theory, communication via social media is dominant during the Covid-19 pandemic. Social media became one of the channels to fulfill the communication needs of the society during the pandemic. Fulfilling this need then becomes a differentiator for the community to choose of social media.